2016
DOI: 10.1080/21655979.2016.1222996
|View full text |Cite
|
Sign up to set email alerts
|

Mining bifidobacteria from the neonatal gastrointestinal tract for conjugated linolenic acid production

Abstract: Conjugated linolenic acid (CLNA) is a family of isomers of linolenic acid with a number of healthassociated benefits, which has been attracting great interest. Microbial CLNA producers are potentially an alternative source of CLNA for human nutrition. In present study, 16 neonate feces were collected and used for Bifidobacteria isolation, from which 25 bifidobacteria isolates were obtained. The bifidobacteria isolates were identified using 16s rDNA sequencing as Bifidobacterium adolescentis, B. breve, B. longu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…While the role of these compounds in CLA production is clear for lactobacilli, research works involving bifidobacterial strains have confirmed their LA/LNAtransforming capacity (47,104,105), but the currently available data suggest that no other metabolites are involved (Fig. 4).…”
Section: Hydratases Are Not Substrate Specificmentioning
confidence: 99%
“…While the role of these compounds in CLA production is clear for lactobacilli, research works involving bifidobacterial strains have confirmed their LA/LNAtransforming capacity (47,104,105), but the currently available data suggest that no other metabolites are involved (Fig. 4).…”
Section: Hydratases Are Not Substrate Specificmentioning
confidence: 99%
“…Compared with other Bifidobacterium species, B. pseudocatenulatum has been shown to be significantly associated with metabolic diseases in both animal experiments (Agusti et al, 2018) and clinical trials (Wu et al, 2017;Zhao et al, 2018). In addition, some B. pseudocatenulatum strains have been noted for their beneficial properties, such as the production of enterolignan, urolithin and conjugated linoleic acid (Yang et al, 2017;Gaya et al, 2018;Peiroten et al, 2019). Therefore, B. pseudocatenulatum is considered as the next-generation probiotic species for its potential beneficial effects.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugated linolenic acid has attracted research interests due to its health‐promoting effects. Many bacterial strains have been identified to biosynthesize CLNA from LNA, such as Butyrivibrio fibrisolvens (Kepler and Tove ), Propionibacterium (Hennessy et al ), Bifidobacterium (Coakley et al ; Gorissen et al ; Hennessy et al ; Yang et al ) and Lactobacillus (Kishino et al ). Although a number of lactobacilli have been reported as high CLNA producers, such as L. plantarum (Kishino et al ; Terán et al ), the exact genetic determinant(s) for CLNA production in lactic acid bacteria was unclear.…”
Section: Discussionmentioning
confidence: 99%